KAJIAN WANITA BERWIRAUSAHA SEBAGAI UPAYA MENINGKATKAN PENDAPATAN KELUARGA - Liana, Yuyuk (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2016)
Crisis situation in our country have an impact on people's lives and it is felt by all segments of society. This condition encourages women to empower themselves so as to assist in the economic level of the family. Women should be smart to see the opportunities that exist and take advantage of its potential ability to become well. Efforts to empower women in entrepreneurship not only from the government but also from individuals who have the wish and desire to continue to progress and welfare of the family. The purposes of the study are (1) To determine the factors of success of women in entrepreneurship (2) To know the motivation of women in entrepreneurship. The population in this study are moms with businesses in the Kelurahan Sisir Kota Batu which amount 45 people.